2010
DOI: 10.1097/jto.0b013e3181c20063
|View full text |Cite
|
Sign up to set email alerts
|

A Phase II Trial of Erlotinib Monotherapy in Pretreated Patients with Advanced Non-small Cell Lung Cancer Who Do Not Possess Active EGFR Mutations: Okayama Lung Cancer Study Group Trial 0705

Abstract: This is the first prospective biomarker study showing that erlotinib therapy for pretreated patients with EGFR-wt tumors seems to have a modest activity with no irreversible toxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
34
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 14 publications
5
34
0
Order By: Relevance
“…First, the BR.21 study showed a survival benefit of erlotinib in NSCLC patients in all statuses, including patients with wild-type EGFR [45]. A phase-II trial showed that the overall survival after erlotinib treatment was 9.2 months in patients with wild-type EGFR who had received chemotherapy previously [46]. The present study showed that the median overall survival after EGFR-TKI treatment was 8.3 months (95% CI 4.3-12.3 months) in patients with wildtype EGFR, which is compatible with previous reports [46].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, the BR.21 study showed a survival benefit of erlotinib in NSCLC patients in all statuses, including patients with wild-type EGFR [45]. A phase-II trial showed that the overall survival after erlotinib treatment was 9.2 months in patients with wild-type EGFR who had received chemotherapy previously [46]. The present study showed that the median overall survival after EGFR-TKI treatment was 8.3 months (95% CI 4.3-12.3 months) in patients with wildtype EGFR, which is compatible with previous reports [46].…”
Section: Discussionmentioning
confidence: 99%
“…A phase-II trial showed that the overall survival after erlotinib treatment was 9.2 months in patients with wild-type EGFR who had received chemotherapy previously [46]. The present study showed that the median overall survival after EGFR-TKI treatment was 8.3 months (95% CI 4.3-12.3 months) in patients with wildtype EGFR, which is compatible with previous reports [46]. Secondly, in the present study, patients with wild-type EGFR and no EGFR-TKI therapy were more likely to be smokers and to have brain metastasis and adrenal gland metastasis than those with wild-type EGFR and EGFR-TKI therapy.…”
Section: Discussionmentioning
confidence: 99%
“…All except one patient had wildtype EGFR [30] . The RR (11.1%), DCR (63.0%), median PFS (2.8 months) and median OS (15.8 months) of our study were superior to those (3.3%, 63.3%, 2.1 months and 9.2 months, respectively) of Okayama Lung Cancer Study Group trial 0705, a Japanese phase II trial of second to fourth line chemotherapy of erlotinib in patients with EGFR wild-type advanced NSCLC [32] . However, our results were similar to those of the previous two subgroup analyses of pemetrexed monotherapy in patients with pretreated advanced non-squamous NSCLC and unknown EGFR mutation status.…”
Section: Phase II Studies Of Combination Of Erlotinib With Pemetrexedmentioning
confidence: 66%
“…These results are remarkably similar (except for OS; survival is commonly better in Japanese NSCLC patients) (10), and also comparable to results in a phase II trial for EGFR mutation-negative Japanese NSCLC. In the trial, the RR, DCR, median PFS and median OS were 3.3%, 60.0%, 2.1 months and 10.7 months, respectively (18). Similarly, Matsuura et al (19) have reported the efficacy of erlotinib as third-line therapy in advanced NSCLC without EGFR mutations.…”
Section: Discussionmentioning
confidence: 97%
“…In our study, ILD was observed in one (2.4%) of 41 patients, and caused this patient's death. In phase II studies of erlotinib therapy conducted in Japan, the incidences of ILD were reported as 6.5% (4 of 62), 2.5% (1 of 40) and 6.7% (2 of 30) (18,25,26). In a prospective epidemiologic cohort study on gefitinib, a higher incidence of ILD was significantly associated with the following factors: elderly, smoker, pre-existing ILD and poor PS (15,27).…”
mentioning
confidence: 99%